Empire, Autonomy and the Polis - Bang, Peter Fibiger (Classica et Mediaevalia, 2026)
This article is a contribution to the debate on the significance of autonomy for the ancient Greek city-state. It argues that one of the most important implications of Hansen’s work on the polis, and his downplaying of autonomy as a constitutive feature, was finally to lay to rest any doubts about the continued vitality of the polis under Roman rule. Ma’s new grand synthesis of the polis seems fully to have taken the consequence of this and expanded its chronological span to include the Roman Empire down to late antiquity. However, there is a paradox in need of resolution here. For at the same time, Ma has decided to re-instate autonomy as a pivotal feature of the polis. How can this be resolved?